Influence of 12 weeks of basketball training on college students' heart function - Yang, Z-T; Kim, S-W; Kim, Y-S; Tang, X; Li, H; Wang, E-L (European review for medical and pharmacological sciences, 2023)
This study aims to investigate the influence of 12 weeks of basketball training on college students' heart function. The subjects were 30 college male basketball players. Carry out 8-week interval training, monitor the training load and interval time of athletes, and strictly control the heart rate during the interval. Before and after training, we used safe and effective experimental instruments - without any damage to the athletes - to detect the relevant indicators of the athletes' physiological functions; hence we compared and analyzed the various indicators before and after training. The time domain indexes Root Mean Square of Successive Differences (RMSSD), Statistically Determined Spatial Drift (SDSD), percentage of NN50 in the total number of NN intervals (PNN50), and Standard Deviation of all NN intervals for all 5-min segment (SDNN) after training were significantly higher than those before training, and the differences were statistically significant (p<0.05). Average (Avag) and Statistically Determined Allocation Weights (SDAW) after training were significantly higher than those before training, the difference was statistically significant (p<0.05); Asymmetry (Asym) and Tension index (TI) were significantly lower than those before training, the difference was statistically significant (p<0.05), Application Information Index (ApInf) had no significant difference (p>0.05). There was no significant difference in shooting hit rate (p>0.05). The speed of the 8-character dribble in the whole field after training was significantly lower than that before training, and the differences were statistically significant (p<0.05). There was no significant difference in average jump height, maximum jump height, average time in the air, and best jump time in the air after training (p>0.05). For the test of athletes' explosive power, five vertical jumps in situ were selected for testing, and the jump height and time in the air of each vertical jump were counted to calculate the maximum and average values of five vertical jumps. The results showed that there was no significant change in the explosive force of the athletes' lower limbs after training. The reason may be that strength training needs to follow the principles of heavy load, specialization, exercise sequence and reasonable interval. The intermittent training method used during training is not specialized in strength training, and the reasonable interval of strength training was not considered in the training process. Intermittent training can increase the tension of the cardiac vagus nerve of college basketball players, increase the cardiac reserve function and the load that the heart can bear, so that the cardiac function can be improved well. It can improve the cardiopulmonary function and aerobic work ability of college basketball players. It can improve the adjustment ability of the heart, lungs, liver, and other organs of college basketball players. It also can increase the load intensity that the central nerve can bear and improve the function of the central nerve and autonomic nerve. The anti-fatigue ability of athletes can be improved. It can improve the speed quality of college basketball players.